Variation in defensive and exploratory behaviors across a rattlesnake (Crotalus scutulatus × viridis) hybrid zone in southwestern New Mexico - Dylan W. Maag; Yannick Z. Francioli; Matthew T. H. Goetz; Lea N. Sanders; Xochitl Lopez; Todd A. Castoe; Gordon W. Schuett; Rulon W. Clark (Scientific Reports)
Abstract Studies on animal temperaments (consistent differences in behaviors across contexts) and behavioral syndromes (suites of correlated behaviors across contexts) have surged in recent decades. Accordingly, behavioral ecologists have gained greater appreciation for their evolutionary role and significance. Yet, despite their importance as potential evolutionary drivers, research focused on temperament and syndromes in shaping hybridization events is vastly understudied. Case studies have shown that hybridization has multiple effects on these phenomena, such as eliminating syndromes present in parental lineages and generating novel syndromes within hybrids. Here, we assessed temperament and syndromes in a naturally occurring rattlesnake hybrid zone (Crotalus scutulatus × viridis). We used laboratory behavioral assays to quantify defensive and explorative behaviors, and tested whether these traits were correlated with spatial and hunting behaviors of free-ranging individuals. C. viridis was more significantly more prone to rattle than C. scutulatus during handling tests. Similarly, hybrid individuals that had a greater proportion of their genome derived from C. viridis were also more prone to rattle. Parental and hybrid snakes exhibited varying syndromes in defensiveness and exploratory behaviors, yet further research is necessary to determine whether they impact hybrid fitness by creating mismatches between temperaments and predation pressures under natural conditions.